Investigating the use of web 2.0 tools and students' cognitive engagement in selected Tanzanian higher learning institutions - Malecela, Issa Omar (Kulliyyah of Education, International Islamic University Malaysia, 2019)
With the availability and affordability of Information and Communication Technology (ICT) devices worldwide, teaching no longer centers on teachers. Higher Learning institutions must find ways to embrace technology applications via the Internet to ensure higher order thinking activities are involved in learning. This study has five folded objectives. The main objective was to investigate the extent of the students' i. actual use of Web 2.0 tools, ii. Practice techno ethics iii. Readiness to embrace technology iv. Cognitively engaged. Secondly, this study attempted to determine the effects of the three variables (actual use of Web 2.0 tools, practice techno ethics and readiness to embrace technology) on cognitive engagement. The Theories of Acceptance Model (TAM) and Web Pedagogical Affordances were used to underpin the research framework. A sequential mixed methods of quantitative and qualitative techniques were deployed. The findings of the two approaches were analyzed, compared and contrasted where qualitative data were used to support the quantitative data. The quantitative data obtained by selecting from the 409 returned responses of the undergraduate students from three universities in Tanzania. University of Dar es Salaam (UDSM), Dar es Salaam Institute of Technology (DIT), and Muslim University of Morogoro (MUM). A proportionate random sampling was employed for quantitative data while interviews were carried out among six students purposely chosen to supplement the quantitative findings of this study. Descriptive statistics using mean scores and percentage, Independent Sample T-test, One-way ANOVA, Post-hoc and Multiple Regression Analysis (MRA) were utilized to address the research questions. The findings reveal that the majority of students (93% to 94%) use Web 2.0 tools for learning involving both low and higher order thinking skills. The majority of the students (82% to 89%) are either already using or are planning to use Web 2.0 tools in learning. The findings also show that most of the students (67% to 89%) practice techno ethics in using Web 2.0 tools in learning. The findings reveal a non-significant difference in the mean scores of technology readiness for ICT related courses and non-ICT related courses. The results of One-way ANOVA reveal a statistically significant difference in students' technology readiness in the mean scores for the three groups. The Post-hoc comparison using Tukey HSD test reveals a statistically significant differences between the Beginner and Intermediate groups, and Beginner and advanced groups indicating knowledge and skills play important role to influence technology readiness. However, there is no statistically significant difference between the Advanced and Intermediate groups as both show similar competencies. In addition, the findings show that students have positive perceptions towards adopting the 21st Century learning activities. Further findings indicate that student technology readiness and practice of techno ethics have effects on students' cognitive engagement. On the contrary, the use of Web 2.0 tools shows non-significant effect on student cognitive engagement despite the actual use is apparent. The study has expanded TAM from the standpoint of cognitive engagement. It also shows empirical evidence that knowledge and skills become the external variable in dealing with TAM on the aspect of readiness in embracing the technology.